Dietary Quality among Tehranian Adults in Relation to Lipid Profile: Findings from the Tehran Lipid and Glucose Study
The prevalence of dyslipidaemia has been increasing in developing countries that are undergoing nutrition transition. However, the association of diet quality and lipid profile has not been well-understood in these countries. The aim of the current study was to compare the ability of three diet quality indicesthe Mediterranean diet scale (MDS), healthy eating index-2005 (HEI-2005), and diet quality index-international (DQI-I) in relation to changes in lipid profile between baseline and 6.7 years of follow-up. Baseline data from two 24-hour dietary recalls provided by 469 adults with mean age of 38.7